Striatal dysfunction marks preexisting risk and medial prefrontal dysfunction is related to problem drinking in children of alcoholics - Heitzeg, Mary M. (2010)
BACKGROUND: Parental alcoholism substantially raises risk for offspring alcoholism, an effect thought to be mediated by a dysregulation in impulse control. Adult alcoholics have alterations in the frontostriatal system involved in regulating impulsive responses. However, it remains controversial whether these alterations reflect pre-existing traits predisposing to problem alcohol use, or are secondary to alcohol involvement. METHODS: Sixty-one 16 to 22 year olds were tested using a go/no-go task during functional MRI. Forty-one had at least one parent with a diagnosis of alcohol use disorder (AUD; FH+) and 20 had no parent with AUD (FH−). Two FH+ subgroups were created to disentangle alcohol involvement from preexisting risk: the FH+ control (n=20) group had low alcohol problems, differing from the FH− group only by family history. The FH+ problem group (n=21) had high alcohol problems. RESULTS: The ventral caudate deactivated during successful inhibition in the FH− but not the FH+ groups, regardless of problem alcohol involvement. Regression analyses showed that ventral caudate deactivation was related to fewer externalizing problems as well as family history. Orbital and left medial prefrontal regions were deactivated in both the FH− and FH+ control groups but not the FH+ problem group. Activation in these regions was associated with alcohol and other drug use. CONCLUSIONS: These findings suggest a preexisting abnormality in ventral striatal function in youth at risk for AUD, which may lead to inappropriate motivational responding; and suggest that with alcohol use, the prefrontal “control” mechanism loses efficiency, further dysregulating the frontostriatal motivational circuitry.